1999
DOI: 10.1038/sj.gene.6363640
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variants of human beta-chemokine receptor 5 (CCR5) promoter: evolutionary relationships and predictable associations with HIV-1 disease progression

Abstract: Variability in the natural history of HIV-1 infection has been repeatedly associated with genetic variants in the betachemokine receptor 5 (CCR5) locus. While CCR5 coding sequences have demonstrated relatively limited variation, sequences of its promoter appear polymorphic in all major populations. Our studies revealed five major CCR5 promoter alleles with distributions that differed widely among the four distinct ethnic groups from Kigali, Rwanda and Bronx, New York. In particular, promoter allele P*0103 (G 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…The prevalence of eight CCR haplotypes detected in the three cohorts ranged from 0% (D) to 37% (C) ( Table 2). Consistent with earlier studies (20,21,70), G*1 was the only haplotype with similar frequencies among Caucasians (2 to 4%) and African-Americans (3%). Haplotype D was largely restricted to AfricanAmericans, and G*2 was far less common in African-Americans than in Caucasians (P Ͻ 0.001 for both comparisons).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…The prevalence of eight CCR haplotypes detected in the three cohorts ranged from 0% (D) to 37% (C) ( Table 2). Consistent with earlier studies (20,21,70), G*1 was the only haplotype with similar frequencies among Caucasians (2 to 4%) and African-Americans (3%). Haplotype D was largely restricted to AfricanAmericans, and G*2 was far less common in African-Americans than in Caucasians (P Ͻ 0.001 for both comparisons).…”
Section: Resultssupporting
confidence: 78%
“…Distinguishing the E/E genotype from the remainder of the P1/P1 genotype combinations largely resolves the apparent discrepancy in the associations of P1/P1 with rapid progression between Caucasians (recessive) and African-Americans (dominant) (2,44). In individuals of African ancestry, higher frequencies of the non-E/E variants encompassed by P1/P1 (20,70) dilute the effect of the less frequent E/E. Thus, the E/E genotype may warrant special attention because of its relative prevalence in major ethnic groups (20,41,52).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the primer sequences in Table 1 were used to determine polymorphism (17); the results showed that only the last allele at the end of the reverse primer 3 was different among the 2 pairs of primers and their forward primers were similar.…”
Section: Methodsmentioning
confidence: 99%